If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -23 = -4x + -9 Reorder the terms: -23 + 3x = -4x + -9 Reorder the terms: -23 + 3x = -9 + -4x Solving -23 + 3x = -9 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -23 + 3x + 4x = -9 + -4x + 4x Combine like terms: 3x + 4x = 7x -23 + 7x = -9 + -4x + 4x Combine like terms: -4x + 4x = 0 -23 + 7x = -9 + 0 -23 + 7x = -9 Add '23' to each side of the equation. -23 + 23 + 7x = -9 + 23 Combine like terms: -23 + 23 = 0 0 + 7x = -9 + 23 7x = -9 + 23 Combine like terms: -9 + 23 = 14 7x = 14 Divide each side by '7'. x = 2 Simplifying x = 2
| -3(2w-8)+10w=16 | | 5+3u=14 | | 42=8p+4(p+5) | | 5(x+10)-(-3+5)=-x-5+14 | | -3(5-X)-3(X-5)= | | 0.055x^2+1.1x=40 | | 8+6x=8+8x-7+3 | | w+7=-5 | | 0.25x+3.4=-7 | | 8=-5+u | | N+4N=225 | | 3(7-2y)=19 | | 20x+5+24x-1= | | 5b-8(4b+5)=176 | | 6(3X+3)-2(9X+9)= | | 84=6(6-8n) | | 30=.5(12)(h) | | .5x+x= | | -2r-6r=8-7r | | 2-15y=5(-3y+2) | | 75C^2-192=0 | | 4x-2=-8+6x+x | | 3p+14=-24+5p | | 5.1q-3.5-4.69=0.5-2.4 | | 4(2-2X)-5(6-X)= | | 2x+-7=0.1(-7+3) | | -x^2+2x+.25=3 | | 3+7(x+8)=87 | | -x^2-2x+.25=3 | | .5x+x+1.25x= | | 11x=20x+8 | | 5(w+1)=3(w+1) |